Genetic insights on the role of telomere dynamics in Chronic Kidney Disease (CKD) regardless of HIV status - Malindisa, Sibusiso Tebogo (My University, 2016)
Telomeres play significant roles in maintaining genome stability, regulating cell proliferation and apoptosis. The role of telomere biology and telomerase reactivation has been studied extensively in cancers. Telomerase has been previously associated with driving chronic kidney disease (CKD) advancement and most frequently due to HIV infection. However, the mechanism by which telomerase activation contributes towards disease progression beyond its canonical function of telomere maintenance is poorly understood. Telomerase is a ribonucleoprotein whose main function is telomere maintenance. Telomerase activity is dependent on expression of the rate-limiting human telomerase reverse transcriptase (hTERT) component. In addition to telomere maintenance, hTERT is implicated in other non-telomere related functions that promote cellular proliferation. Expression of hTERT is predominantly regulated at the transcription level where variation in promoter and minisatellite (MNS16A) sequences alter its expression. This variation has been implicated to confer susceptibility to diseases such as cancer and ageing disorders in non-African populations. Data on variation and pathogenicity of telomere-associated genes in African populations is limited and warrants further research. Thus bioinformatics analysis was performed to elucidate variation within the human TERT gene and promoter in different populations. The promoter, MNS16A and relative telomere length (RTL) were also evaluated in 159 African study participants with and without CKD. TERT common variants are equally distributed across populations with limited data on connection to the effects of the variants in African populations. Further bioinformatics analyses revealed significant difference (p<0.0001) in distribution of promoter variant rs2853669 between African and non-African populations. No common promoter mutations were identified in our study population. Interestingly, the long MNS16A variant suggested to increase TERT expression was significantly overrepresented in individuals with CKD regardless of HIV status. For the first time, a strong association of the long MNS16A variant with CKD regardless of HIV status is reported, implicating MNS16A as a potential risk factor in CKD.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of requirements for the degree of Master of Science in the School of Molecular and Cell Biology. Johannesburg, 2016.
Keywords: Chronic renal failure.; Kidneys--Disease.; HIV infections.